Aristolochia elegans Mast. (Aristolochiaceae) â A new angiospermic record for Bangladesh - Rahman, Md. Oliur; Afroz, Sumona; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. Keywords: Aristolochia elegans Mast., New record, Bangladesh Â  DOI: 10.3329/bjpt.v15i2.1753 Â  Bangladesh J. Plant Taxon. 15(2): 155-158, 2008 (December)